Research on Green Logistics Development in Chengdu-Chongqing Region under the Perspective of Game Theory - Geng, Qi; Zhao, Wanru (International Journal of Global Economics and Management, 2024)
Chengdu-Chongqing Twin Cities Economic Circle is an important growth pole for the formation of high-quality development in western China and has a unique and important strategic position in the overall situation of national development. Chengdu-Chongqing two places not only vigorously promote the construction of logistics corridors and infrastructure connectivity, but also promote the logistics of all kinds of factors of production, including reasonable flow and efficient agglomeration, and strive to promote the Chengdu-Chongqing two places to the green logistics, cost reduction and efficiency to make effective exploration. The paper first analyzes the current situation and problems of green logistics construction in the Chengdu-Chongqing area, and then establishes an evolutionary game model between the government, enterprises, and consumers based on the game theory perspective, to try to put forward reasonable suggestions for the development and construction of green logistics in Chengdu-Chongqing area.